Development of Teaching Materials Oriented to Numeracy Literacy and Socio-Cultural Literacy for Madrasah Ibtidaiyah - Fadila, Abi; Hakim, Rahman; Putra, Rizki Wahyu Yunian; Ambarwati, Riyama (Jurnal Pendidikan Matematika, 2024)
In this modern era, although technology has brought significant changes to education, there remains a gap in the implementation of numeracy and socio-cultural literacy in Madrasahs in Indonesia, contributing to students' low numeracy literacy skills. The government has introduced the Indonesian Madrasah Competency Assessment Program (AKMI), but challenges in developing innovative and needs-based teaching materials persist. Therefore, new strategies are needed to enhance students' literacy in diverse contexts, such as numeracy literacy-oriented teaching materials. This study aims to develop teaching materials oriented towards numeracy and socio-cultural literacy for Madrasah Ibtidaiyah using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research instruments included expert validation sheets to evaluate the feasibility of the teaching materials and questionnaires to assess the product's attractiveness from students' perspectives. The feasibility of the teaching materials was evaluated by three groups of experts: material, media, and socio-cultural specialists. The validation results showed average scores of 3.59 for the material aspect, 3.46 for the media aspect, and 3.48 for the socio-cultural aspect on a 4-point scale, indicating that the teaching materials met the feasibility criteria. Meanwhile, the attractiveness of the teaching materials was assessed based on student responses through questionnaires involving two trial groups: a small group of 10 students with an average attractiveness score of 3.59 and a larger group of 20 students with an average attractiveness score of 3.62. The results of the study indicate that the developed teaching materials are feasible to use based on expert validation and are considered attractive by students. Thus, the development of these teaching materials is expected to contribute positively to the learning process in Madrasah Ibtidaiyah. Di era modern ini, meskipun teknologi telah membawa perubahan signifikan dalam pendidikan, masih terdapat kesenjangan dalam penerapan literasi numerasi dan sosial budaya di Madrasah di Indonesia, yang berdampak pada rendahnya kemampuan literasi numerasi siswa. Upaya pemerintah melalui Program Asesemen Kompetensi Madrasah Indonesia (AKMI) telah dilakukan, tetapi tantangan dalam mengembangkan bahan ajar yang inovatif dan sesuai kebutuhan tetap ada. Oleh karena itu, diperlukan strategi baru untuk meningkatkan literasi siswa dalam konteks yang beragam. Penelitian ini bertujuan untuk mengembangkan bahan ajar yang berorientasi pada literasi numerasi dan sosial budaya untuk Madrasah Ibtidaiyah dengan menggunakan model ADDIE (Analisis, Desain, Pengembangan, Implementasi, Evaluasi). Instrumen penelitian mencakup lembar validasi ahli untuk mengevaluasi kelayakan bahan ajar dan angket untuk menilai tingkat kemenarikan produk dari sudut pandang mahasiswa. Kelayakan bahan ajar dievaluasi oleh tiga kelompok ahli, yaitu ahli materi, media, dan sosial budaya. Hasil validasi menunjukkan rata-rata skor 3,59 untuk aspek materi, 3,46 untuk aspek media, dan 3,48 untuk aspek sosial budaya pada skala 4, yang menunjukkan bahwa bahan ajar memenuhi kriteria kelayakan (kategori”layak”). Sementara itu, kemenarikan bahan ajar dinilai berdasarkan respons mahasiswa melalui angket. Penilaian dilakukan oleh dua kelompok uji coba: kelompok kecil yang terdiri dari 10 mahasiswa dengan rata-rata penilaian kemenarikan 3,59 dan kelompok besar yang terdiri dari 20 mahasiswa dengan rata-rata penilaian kemenarikan 3,62. Hasil penelitian menunjukkan bahwa bahan ajar yang dikembangkan layak digunakan berdasarkan validasi para ahli dan dinilai menarik oleh mahasiswa. Dengan demikian, pengembangan bahan ajar ini diharapkan dapat memberikan kontribusi positif terhadap proses pembelajaran di Madrasah Ibtidaiyah.